2019
DOI: 10.1101/827311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Admixture/fine-mapping in Brazilians reveals a West African associated potential regulatory variant (rs114066381) with a strong female-specific effect on body mass- and fat mass-indexes

Abstract: Admixed populations are a resource to study the global genetic architecture of complex phenotypes, which is critical, considering that non-European populations are severely underrepresented in genomic studies. Leveraging admixture in Brazilians, whose chromosomes are mosaics of fragments of Native American, European and African origins, we used genome-wide data to perform admixture mapping/fine-mapping of Body Mass Index (BMI) in three population-based cohorts from Northeast (Salvador), Southeast (Bambuí) and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The three models were adjusted by age, sex, BMI, and global African ancestry. We used an additive model that considers the number of inferred African, European or Native American ancestry copies (0, 1 or 2) carried by an individual for each window [ 27 ]. We used PLINK software [ 26 ] to perform linear regressions.…”
Section: Methodsmentioning
confidence: 99%
“…The three models were adjusted by age, sex, BMI, and global African ancestry. We used an additive model that considers the number of inferred African, European or Native American ancestry copies (0, 1 or 2) carried by an individual for each window [ 27 ]. We used PLINK software [ 26 ] to perform linear regressions.…”
Section: Methodsmentioning
confidence: 99%
“…This approach allows not only the validation (or not) of already identified IVs, but most importantly, the discovery of new IVs of relevance in Latin America. In fact, an admixture mapping study carried out on participants of the EPIGEN-Brasil consortium recently reported a low frequency variant of chromosome 13 strongly associated with body mass index (BMI) in females [17]. This variant, very rare in Europeans, exhibited a notably larger effect size in Brazil than that of SNPs in fat mass and obesity-associated gene (FTO), one of the genes with the most compelling association amongst Europeans.…”
Section: Generating New Information Locally: Genome-wide Association and Sequencing Studies In Latin American Populationsmentioning
confidence: 99%
“…Third, there was limited mention of confounding by population stratification, despite the well-known admixed background of Brazilians; nonetheless, some studies attempted to take this into account, adjusting for skin color, race, or ethnicity. Only a couple of studies ran models adjusted for principal components [38] or genetic ancestry [17]. Fourth, there is a very uneven, yet not unexpected, distribution of studies throughout the country, with concentration on the south and southeast regions, and on women and children.…”
Section: Making Sense Of Small Local Studiesmentioning
confidence: 99%